Evaluating Relation Between Cranial Base And Mandible In Class II Skeletal Patients (International Journal of Environmental Sciences, 2025)
Background: Skeletal Class II malocclusion represents one of the most prevalent orthodontic conditions, affecting approximately 15-20% of the population. The relationship between cranial base morphology and mandibular positioning has been a subject of considerable interest in orthodontic research, yet the precise mechanisms underlying this association remain incompletely understood.Objective: This study aimed to evaluate the morphological relationship between cranial base parameters and mandibular characteristics in Class II skeletal patients compared to Class I controls, and to determine the clinical significance of these associations.Methods: A retrospective cephalometric analysis was conducted on 120 subjects (60 Class II skeletal patients and 60 Class I controls) aged 18-25 years. Lateral cephalometric radiographs were analyzed using digital cephalometric software. Cranial base measurements included anterior cranial base length (S-N), posterior cranial base length (S-Ba), cranial base angle (N-S-Ba), and cranial base inclination (S-N/FH). Mandibular parameters assessed were mandibular length (Co-Gn), ramus height (Co-Go), mandibular body length (Go-Me), and mandibular plane angle (Go-Me/FH).Results: Class II patients demonstrated significantly longer anterior cranial base length (71.2 ± 3.8 mm vs. 68.9 ± 3.2 mm, p < 0.01) and posterior cranial base length (43.8 ± 2.9 mm vs. 41.5 ± 2.6 mm, p < 0.05) compared to controls. The cranial base angle was significantly more obtuse in Class II subjects (131.4 ± 4.2° vs. 128.7 ± 3.9°, p < 0.01). Mandibular length was reduced in Class II patients (105.3 ± 5.4 mm vs. 109.8 ± 4.9 mm, p < 0.001), with significant correlations observed between cranial base angle and mandibular length (r = -0.68, p < 0.001).Conclusion: This study demonstrates significant morphological associations between cranial base structure and mandibular characteristics in Class II skeletal patients. The findings suggest that cranial base morphology may contribute to the development of Class II skeletal patterns, with clinical implications for treatment planning and prognosis.